ADAPTASI SOSIAL SANTRI PUTRA KELAS X MA DI PONDOK PESANTREN KHULAFAUR RASYIDIN SUNGAI RAYA - Mudiansyah, Aris; Bahari, Yohanes; Al Hidayah, Riama (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of this research is "social adaptation of male students of class 10 of Madrasa Aliyah at the islamic boarding school Khulafar Rasyidin Sungai Raya". The problem in this research is the students' social adaptation. The purpose of this research is to find out social adaptation of the islamicÂ  students of class 10 in overcoming environmental challenges and the process of adaptation to norms. Form of this research is a descriptive qualitative research. Techniques of data collection are direct observation, interview and documentary study. The research finding shows the success of the students of class 10 in adaptation towards the school environmental, particularly male students; (1) the students could overcome the challenges of the school both positively and negatively. (2) the male students of class 10 could adapt to norms of religion, politeness, morality embraced in the boarding school, although written school rules, certain group of students they remain to break.Keywords: Adaptation, Islamic Boarding School, Male StudentsÂ